Estimation of Money Demand Function for Reserve Money in Serbia - Vukovic, Marija; Miletic, Ljiljana; Maravic, Jelena (Industrija, 2016)
This paper examines the relevance of the function of demand for reserve money in the Republic of Serbia in the period from January 2002 to December 2015 (168 monthly observations). Our research showed positive and statistically significant coefficients for variables gross domestic product at constant prices and deposit interest rates. The model showed the expected and significant sign for inflation that is a negative correlation between inflation and demand for reserve money. The research results suggest that increase of expected inflation by 1%, with the other variables unchanged, will reduce demand for reserve money for 754 million RSD. The higher the expected inflation, the more pronounced is the recourse to real forms of assets.